Aplikasi Sistem Informasi Dan Pemetaan Daerah Pariwisata Berbasis Web - FNU Nurahaliza; Mulyadi Mulyadi (Jurnal Tika, 2022)
Increase public awareness of regional potential, this tourism information system includes tourism development and website-based tourism. Tourism is a broad term that refers to various tourism activities that are supported by various facilities and services provided by the community, business world, government, and local government. Aceh tourism has a lot of tourism potential, but few people realize it. Social media, blogs and websites are all used to promote tourism in Aceh. However, there is no system that can store all the data and display a map of the location of attractions and all other aspects of tourism. This is necessary because there is no system that facilitates the acquisition of knowledge and tourist destinations. This encourages to build an information system that can provide complete information to the public and tourists who want to visit Aceh. The results of this study show tourist attractions, lodging and restaurants and can be a consideration for choosing tourist attractions in Aceh. In addition, the system can display various information such as name, address, description, tourist destination, and route.